2019
DOI: 10.1111/sms.13388
|View full text |Cite
|
Sign up to set email alerts
|

Damage and the repeated bout effect of arm, leg, and trunk muscles induced by eccentric resistance exercises

Abstract: This study compared nine resistance eccentric exercises targeting arm, leg, and trunk muscles in one session for changes in maximal voluntary isometric contraction strength (MVC), delayed onset muscle soreness (DOMS), plasma creatine kinase (CK) activity, and myoglobin (Mb) concentration after the first and second bouts.Fifteen sedentary men (20-25 years) performed 5 sets of 10 eccentric contractions with 80% of MVC load for the elbow flexors (EF), elbow extensors (EE), pectoralis, knee extensors (KE), knee fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 34 publications
6
72
1
Order By: Relevance
“…The participant was instructed to flex the elbow joint maximally for 3 s, and this was repeated three times with a 45-s rest between attempts. The peak value was defined as the highest value during the 3-s contraction, and the highest value of the three peak values was used to determine the dumbbell weight (15,16).…”
Section: Progressive Trainingmentioning
confidence: 99%
“…The participant was instructed to flex the elbow joint maximally for 3 s, and this was repeated three times with a 45-s rest between attempts. The peak value was defined as the highest value during the 3-s contraction, and the highest value of the three peak values was used to determine the dumbbell weight (15,16).…”
Section: Progressive Trainingmentioning
confidence: 99%
“…However, it remains controversial whether the intensity of the exercise was consistent with the markedly elevated levels of serum CK (Honda et al, 2017 ). Chen et al ( 2019 ) found with resistance training, that CK levels are higher when training is on consecutive days. Thus, subjecting CrossFit ® training practitioners to a higher volume and intensity of training for successive days may expose the practitioner to the risk of damage associated with muscle cell necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…angle, ROM, MVIC, SOR, muscle circumference, plasma CK and myoglobin levels, and ultrasound echo intensity between elbow flexors and knee extensors after an extension contraction exercise reported that the knee extensors showed significantly lower values for all the measured items compared to the flexor muscles. Chen et al 20) , who compared sensitivity to EIMD among nine muscles (elbow flexors, elbow extensors, pectoralis, knee extensors, knee flexors, plantar flexors, latissimus, abdominis, and erector spinae), reported that the elbow flexor was the muscle most susceptible to pain, whereas the plantar flexor muscle came sixth in the list. Another previous study 21) reported that the degree of EIMD was influenced by the frequency of exposure to eccentric contraction on a daily basis; thus, the EIMD of lower limb muscles, which are used on a daily basis for eccentric loads such as running, jumping, and walking down stairs, show significantly less EIMD compared to the upper limbs.…”
Section: Discussionmentioning
confidence: 99%